FROM EMPOWERMENT TO DEPENDENCY: EXAMINING THE IMPACT OF CORPORATE SOCIAL RESPONSIBILITY ON COMMUNITY INDEPENDENCE - Dadan Ramdhan; Amirah Azzahra; Muhammad Rafi Thoriq (RADJA PUBLIKA, 2026)
This study aims to analyze corporate social responsibility (CSR) implementation motives and their implications for community self-reliance. The study employed a qualitative approach with a literature review method, analyzing scientific articles, sustainability reports, and CSR-related regulations. The results indicate that CSR implementation is influenced by three primary motives: regulatory compliance, corporate image building, and business interests through the creating shared value (CSV) approach. Although CSR contributes to improving community well-being, its impact on self-reliance remains limited. This is due to the dominance of aid-based approaches, low community participation, and a program orientation that emphasizes the legitimacy and strategic interests of the company over capacity building. As a result, CSR tends to produce dependency and pseudo-impact, where improvements in well-being are not accompanied by sustainable improvements in community capacity. Therefore, the effectiveness of CSR in promoting self-reliance depends heavily on participatory program design, based on local needs, and oriented toward long-term capacity building.